The relationship between men’s attitudes on seeking mental health services and gender role conflict : sn icelandic observation - Eyjólfur Sverrisson 1992- (2022)
There is no doubt that when men try to live up to the standards or expectations of what is perceived to be a ‘‘masculine man‘‘, it does reflect poorly on various areas of their life, whether those expectations are put forth by themselves or by society. The purpose of the current study was to examine the relationship between men‘s attitudes towards seeking mental health services and gender role conflict. Age, education and marital status differences were also explored. The sample that was used consisted of 76 male only participants, all over the age of 18. All participants resided in Iceland. Data was gathered using an online based questionnaire distributed via social media. Results demonstrated a moderate negative correlation between attitudes and gender role conflict. The relationship was statistically significant. Results further showed that married men had less favourable attitudes compared to men of other marital status. There were no age or education differences visible. Strengths and limitations were discussed in addition to directions for future research. Keywords: gender role conflict, psychological help-seeking attitudes, mental health services, masculinity, femininity. Það liggur enginn vafi á því að þegar karlmenn reyna að uppfylla þá staðla eða þær væntingar sem gert er ráð fyrir að þurfi til til þess að þykja ,,karlmannslegur‘‘, þá bitnar það á ýmsum þáttum í þeirra lífi. Þessar væntingar geta ýmist vera lagðar fram af þeim sjálfum eða samfélaginu. Markmið þessarar rannsóknar var að skoða sambandið milli viðhorfa karlmanna við því að sækja sér sálfræðiaðstoð og kynjahlutaverkaágreinings. Munur milli aldurs, menntunar og hjúskaparstöðu var einnig athugaður. Úrtakið samanstóð af 76 þátttakendum, eingöngu karlmenn 18 ára og eldri. Allir þátttakendur höfðu búsetu á Íslandi. Gagnaöflun átti sér stað með rafrænum spurningalista sem sendur var út á samfélagsmiðlum. Niðurstöður sýndu fram á neikvæða fylgni af meðal styrk milli viðhorfa og kynjahlutverkaágreinings. Sambandið var tölfræðilega marktækt. ...